Cross-Cultural Adjustment: A Case Of Thai Expatriates In Indonesia - Rodsai, Tayaphon; Stoffers, Jol; Talim, Margaretha Banowati (Journal of Applied Business Research, 2017)
This study empirically examines individual and organizational factors that influence expatriates’ cross-cultural adjustment and job performance. The study was a quantitative research from 117 Thai expatriates who work in Thai multinational companies (MNC) located in Indonesia.The results of the study indicated that financial perceived organizational support influence positively towards Thai expatriates’ overall cross-cultural adjustment in Indonesia. This study found that cross-cultural training influenced positively towards Thai expatriates’ adjustment. A causal relationship between the predicting variables of cross-cultural adjustment and Thai expatriates’ job performance was not found.Results suggest important consequences for management strategies providing support to Thai expatriate employees increasing their adjustment in Indonesia.
Keywords: Cross-Cultural Adjustment; Job Performance; Cultural Intelligence; Language Ability; Perceived Organizational Support; Thai Expatriate; Indonesia